CUSTOMER RELATIONSHIP MANAGEMENT, CUSTOMER VALUE AND PRODUCT QUALITY AND ITS IMPACT ON CUSTOMER SATISFACTION: LITERATURE STUDY - Ni Nyoman Padang Cakra Binaraesa; Hwihanus (Lampung Selatan: Sekolah Tinggi Ilmu Ekonomi Muhammadiyah Kalianda, 2023)
Customer Relationship Management (CRM) and Customer Value can be used as a tool to increase customer satisfaction while still paying attention to product quality and paying attention to dynamic customer desires. This study uses a qualitative descriptive analysis literature study approach. This study reviews the 47 articles obtained and as many as 30 selected scientific articles with a focus on the period 2018 to 2022. The results of this study are having good relationships with customers in the long term, and applying the concept of Customer Relationship Management (CRM), Customer Value which provides value benefits and perceived by consumers and paying attention to product quality will have an impact on company profits by having satisfied consumers.